The The Association Of Obesity With The Incident Of Flat Foot In Adults: A Cross-Sectional Study Of Academic Community In Jambi City - Susan Tarawifa; Rina Nofri Enis; Nyimas Natasha Ayu Shafira; Anggelia Puspasari; Syatria Esa Putra (FAKULTAS KEDOKTERAN DAN ILMU KESEHATAN UNIVERSITAS JAMBI, 2023)
ABSTRACT Background: Flat feet is a foot deformity that refers to the loss of the mid-length of the foot. This can cause pain, stiffness, discomfort, and irritation in the ankles and feet. This study attempts to determine the relationship between obesity and the issue of flat feet in the academic community of the Faculty of Medicine and Health Sciences (FKIK) Universitas Jambi (UNJA) Medical Study Program. Method: This observational analytic research used a cross-sectional design with samples of 102 academics from the FKIK UNJA Medical Study Program. The primary data consisted of body weight, height, BMI, and soles of the feet. Bivariate analysis using the Chi-square test. Result: The incidence of flat feet is 20.6%, and 45,7% of flat feet are obese. There is an association between obesity and the incidence of flat foot in the academic community of the FKIK UNJA Medical Study Program. Conclusion: There is a significant relationship between body mass index and the incidence of flat feet in the academic community of the FKIK Jambi University Medical Study Program.